2019
DOI: 10.1038/s41598-019-47312-3
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the functional role of Mycobacterium smegmatis recX in stress response

Abstract: The RecX protein has attracted considerable interest because the recX mutants exhibit multiple phenotypes associated with RecA functions. To further our understanding of the functional relationship between recA and recX , the effect of different stress treatments on their expression profiles, cell yield and viability were investigated. A significant correlation was found between the expression of Mycobacterium smegmatis recA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…High degree of hypoxia can induce cell cycle arrest in a variety of cell types 45 , while CCNA2 is a key factor in cell cycle and could be up-regulated induced by hypoxia to promote cell proliferation 39 . Also, acute stress caused by hypoxia arrests DNA replication and triggers DNA damage 46 , while DNA replication supported by the complexes of CCNA2‐CDK could push forward the cell cycle in the S‐phase 47 . Besides, hypoxia has been reported to suppress DNA repair through homologous recombination 48 , while CCNA2 is located at sites of DNA double-strand breaks (DSB) and plays a role in homologous recombination 49 .…”
Section: Discussionmentioning
confidence: 99%
“…High degree of hypoxia can induce cell cycle arrest in a variety of cell types 45 , while CCNA2 is a key factor in cell cycle and could be up-regulated induced by hypoxia to promote cell proliferation 39 . Also, acute stress caused by hypoxia arrests DNA replication and triggers DNA damage 46 , while DNA replication supported by the complexes of CCNA2‐CDK could push forward the cell cycle in the S‐phase 47 . Besides, hypoxia has been reported to suppress DNA repair through homologous recombination 48 , while CCNA2 is located at sites of DNA double-strand breaks (DSB) and plays a role in homologous recombination 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we checked ΔdisA and Δpde mutants' survival patterns under different stresses and found that varying c-di-AMP concentration could play a definite role which is linked to underlying pathways yet to be discovered. The Δpde mutant was found to be very sensitive to UV irradiation compared to WT, possibly due to RecA enzyme's functional deficiency (46) and the ΔdisA strain has better survival under identical conditions. demonstrated.…”
Section: Somentioning
confidence: 99%
“…Several studies have demonstrated an alternative role for recX in the DNA repair of recombination performed by RecA (Pages et al 2003;Ragone et al 2008;Prasad et al 2019). The absence of RecX severely impaired the natural transformations in both plasmid and chromosomal DNA.…”
Section: Discussionmentioning
confidence: 99%
“…RecX abrogates RecA•ATP-hydrolysis, and strand exchange promoted by RecA and RecX might act as an anti-recombinase to inhibit inappropriate recombination repair during normal DNA metabolism (Venkatesh et al 2002;Yakimov et al 2017). Previous work revealed that RecX is also involved in regulating the Mycobacterium smegmatis stress response (Prasad et al 2019). However, the regulatory mechanisms of RecX have been less studied in the biocontrol bacterium L. enzymogenes.…”
Section: Discussionmentioning
confidence: 99%